PENGARUH LIVE STREAMING SHOPEE EDISI BIG RAMADHAN SALE 2024 TERHADAP KEPUTUSAN PEMBELIAN SAAT SAHUR PADA MAHASISWA PERANTAUAN DI SURABAYA - Putri, Andini; Tatak Setiadi (Universitas Negeri Surabaya, 2025)
This study aims to analyze the influence of live streaming on purchasing decisions of out-of-town students in Surabaya during the Shopee Big Ramadhan Sale 2024 event. Involving 334 respondents, this study evaluates the extent to which product quality indicators, host credibility and promotions (discounts & time) can influence consumer purchasing decisions. The research approach used in this study is a quantitative method using data analysis techniques in the form of Classical Assumption Test, Normality Test, Heteroscedasticity Test, Linearity Test. The results of the study show that live streaming promotions have a positive and significant influence on purchasing decisions, with a contribution of 43.1% and sahur time during Ramadhan is an effective